The mexican war : a history of its origen, and a detailed account of the victories wich terminated in the surrender of the capital ; with the official despatches of the generals. To which is added, the Treaty of Peace, and valuable tables of the strength and losses of the United States Army. - Mansfield, Edward Deering (2015)
UANL